Seasonal steady-state budgets of nutrients and stoichiometric calculations in an Eastern Mediterranean lagoon (Papas Lagoon-Greece) - KRASAKOPOULOU, E.; PAGOU, K. (Mediterranean Marine Science, 2011)
The Papas Lagoon is an enclosed, small shallow water body in western Greece. The lagoon is naturally affected by eutrophication phenomena, but occasionally during the summer season, dystrophic crises occur, related to the decomposition of large beds of macroalgae. Physicochemical data collected monthly, from June 1998 to September 1999, were compiled and coupled with historical meteorological data, in order to construct seasonal water, salt and nutrients budgets using a single box single layer LOICZ model. Nutrients and other hydrochemical parameters exhibit great spatial and temporal variations. The non-conservative dissolved inorganic phosphorus flux (ΔDIP) is always positive, thus indicating that the system acts as a net source of DIP for the adjacent coastal waters. Higher values were estimated uring summer and autumn, probably due to organic matter mineralisation and release of DIP from surficial sediments in the reduced environment. In contrast to the ΔDIP, the non-conservative balance of dissolved inorganic nitrogen (ΔDIN) is negative for most of the year, except for the summer, indicating the dominance of DIN removal processes in the Papas Lagoon. The Ulva growth and decomposition processes seem likely to be of essential importance for the evaluation of the non-conservative DIN fluxes. During the investigated period the amount of organic carbon respired and mineralized is greater than that produced by gross photosynthesis and the Papas Lagoon is a net heterotrophic system. Losses of DIN via denitrification appear to dominate over its inputs through nitrogen fixation throughout the year.